Language learning strategies used by Indonesian pharmacy students beyond the classroom - Noprival, Noprival; Alfian, Alfian; Soma, Robi; Rozelin, Diana; Mahir Muttaqin, Wildan (SALEE: Study of Applied Linguistics and English Education, 2023)
Although many scholars have conducted studies on Language Learning Strategies (LLS) around the world, this issue is still new in the context of English for Medical Purposes (EMP), especially as used by Indonesian pharmacy students. Further, a majority of those previous studies have been conducted using exclusively quantitative research. In response to these empirical and methodological gaps, the current research adopts a qualitative case study to examine the LLS used by Indonesian pharmacy students, as guided by Oxford’s (1990) LLS theory. This study utilized in-depth interviews to gather information from participants. The thematic analysis of the semi-structured interviews presented five major strategies used by learners: engaging in social interaction, enriching their vocabulary, using web based language learning, practicing through online platforms, and employing fun learning. Findings demonstrate that most of their learning strategies involve employing online platforms.